A Discourse Stylistics Analysis on the Regularities in Dan Brown’s The Da Vinci Code - Mardliya Pratiwi Zamruddin; Chris Asanti; Burhanuddin Arafah (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The aim of this study was to identify the regularities of Dan Brown’s novel: The Da Vinci Code based on stylistic and narratological approach. To attain the regularities/irregularities that occurred in the novel and to frame the style of the novelist, a qualitative research design was employed. The data were gathered from the novel; The Da Vinci Code, by taking into account of stylistic categories. The results of the study revealed the occurrences and the forms of regularities in the novel The Da Vinci Code by Dan Brown which mirrored the style of the novelist. Dan Brown's powerful style is evident in the large number of noun phrases used in this novel. In every case, he uses noun phrases repeatedly and consistently. When describing a person's traits, he employs the noun phrase to point to occupations, specific names, locations, and items, and to designate personal pronoun.